Educational Spread of Buntet Boarding School in A Rural Area - Chofyan, Ivan; Agustina, Ina Helena; Chamid, Chusharini; Rosenda, Diden; Saputra, Dika Lukmana; Sukmawati, Lathansya Mulya; Yanto, Muhtadin (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
The Buntet Islamic Boarding School was first founded in 1750 by Kyai Muqayim bin Abdul Hadi, known as Mbah Muqayim. He was the chief of the Kanoman Palace. Since its establishment, this pesantren has had relations with the palaces in Cirebon. The history and tradition of this boarding school are tied to the growth of Islam in West Java. The purpose of this study is to investigate how education is disseminated at Buntet pesantren in rural areas. The study used a mixed-methods technique, which combines qualitative and quantitative data analysis. Employing the snowball method to get information from informants while doing field observations. Data processing involves categorizing data in accordance with groups of recurring themes. Additionally, map data was gathered and processed using ArcGIS software to observe changes in space from 2002 to 2022. The findings demonstrates that the transmission of education can build the social character of the village community as well as the propagation of spatial changes.